Exploring the Doctrine of Salvation in Evangelical Theology and Its Relevance in the Postmodern Era. - Willyam, Verry (Jurnal Teologi Trinity, 2024)
Humans are fragile beings, and even the knowledge they possess may not save them from eternal punishment. Humanity needs God for salvation, once and for all, a salvation that cannot be lost, as outlined in the doctrine of salvation in Evangelical Theology. This paper aims to historically elaborate on the concept of salvation in Evangelical theology and the biblical foundations of Evangelical beliefs, where it is not salvation that is lost, but rather humans themselves who are lost from God's presence for not accepting Christ as their Savior. Utilizing a descriptive qualitative method with a literature study approach, it gathers sources as evidence of the long journey of the Christian faith. Ultimately, through Evangelical doctrinal perspectives, it can open doors to proclaim salvation for everyone amid the challenges of the times.